1988
DOI: 10.1073/pnas.85.21.8355
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic determination of kinetic parameters for the interaction between polypeptide hormones and cell-surface receptors in the perfused rat liver by the multiple-indicator dilution method.

Abstract: Hepatic elimination of epidermal growth factor (EGF) via receptor-mediated endocytosis was studied by a multiple-indicator dilution method in the isolated perfused rat liver, in which cell polarity and spatial organization are maintained. In this method EGF was given with inulin, an extracellular reference, as a bolus into the portal vein, and dilution curves of both compounds in the hepatic vein effluent were analyzed. Analysis of the dilution curve for EGF, compared with that for somatostatin, which showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…2 and 4), indicating that the probability of an EGF-receptor complex on the cell-surface being internalized per minute is independent of the classes ofbinding sites, as we found previously (14). However, in other studies (9,15,18,20), we could not find multiple binding sites in any experimental system, although nonspecific (unsaturable) binding was observed. We estimated that the equilibrium dissociation constant, Kd, was a few nanomolar in either isolated hepatocytes (18) or isolated liver membrane vesicles (20) and was 18 nM in perfused rat liver (9 McClain and Olefsky (22) have reported that there exist two independent pathways for insulin internalization in hepatocytes and hepatoma cells.…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…2 and 4), indicating that the probability of an EGF-receptor complex on the cell-surface being internalized per minute is independent of the classes ofbinding sites, as we found previously (14). However, in other studies (9,15,18,20), we could not find multiple binding sites in any experimental system, although nonspecific (unsaturable) binding was observed. We estimated that the equilibrium dissociation constant, Kd, was a few nanomolar in either isolated hepatocytes (18) or isolated liver membrane vesicles (20) and was 18 nM in perfused rat liver (9 McClain and Olefsky (22) have reported that there exist two independent pathways for insulin internalization in hepatocytes and hepatoma cells.…”
Section: Discussioncontrasting
confidence: 46%
“…We have been analyzing the kinetics of the hepatic handling of a model polypeptide, epidermal growth factor (EGF), in rats in vivo (1, 2, 4), in perfused liver (9,14,15), in isolated hepatocytes (18,19), and in isolated liver plasma membrane vesicles (20). We have shown that liver plays a major role in the elimination of EGF from the circulating blood (1, 2) and suggested that the liver may regulate the plasma concentration of EGF via receptor-mediated endocytosis (1, 2, 15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations